2018
DOI: 10.17556/erziefd.402532
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmenlerinin Bireyselleştirilmiş Eğitim Programı (BEP) Hazırlamada Karşılaştıkları Güçlükler ve Kaynaştırma Uygulamalarına İlişkin Görüşlerinin Değerlendirilmesi

Abstract: Aim of this study is evaluating difficultiesThis study aims to evaluate difficulties the classroom teachers working in Muğla city center encountered in the process of preparing individualized education programs and their problems regarding revisions to be made in inclusive practices. In this study a descriptive research design was used and data were collected by using "Socio-Demographic Information Form", "Scale of Determining Difficulties in the Process of Preparing İndividüalizme Education Program (IEP)" dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 12 publications
(4 reference statements)
0
1
0
9
Order By: Relevance
“…Under the theme "RAM processes", a total of six sub-themes such as screening, sending, identification, settlement, evaluation, and monitoring were constituted. When the studies conducted on screening process were analyzed, it revealed that screening was made twice a year (Kamen-Akkoyun, 2007) and it also became clear that screening was not sufficient and widespread (Avcıoğlu, 2012). It is stated that the reports prepared by schools encompassing students' information and observations within the scope of sending process are submitted to RAMs.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Under the theme "RAM processes", a total of six sub-themes such as screening, sending, identification, settlement, evaluation, and monitoring were constituted. When the studies conducted on screening process were analyzed, it revealed that screening was made twice a year (Kamen-Akkoyun, 2007) and it also became clear that screening was not sufficient and widespread (Avcıoğlu, 2012). It is stated that the reports prepared by schools encompassing students' information and observations within the scope of sending process are submitted to RAMs.…”
Section: Methodsmentioning
confidence: 99%
“…Tarama sürecine ilişkin araştırmalar incelendiğinde tarama çalışmalarının yılda iki defa yapıldığı (Kamen-Akkoyun, 2007) ve aksi yönde bir bulgu olarak taramaların yetersiz olduğu ve yaygın olmadığı (Avcıoğlu, 2012) bulgularına ulaşılmıştır. Bu sürece yönelik aynı kurum çalışanlarının 52,7'sine göre tarama çalışalarının yapıldığı, %32.7'sine göre ise yapılmadığı (Tiryakioğlu, 2009) şeklinde bulgu dahi görülmektedir.…”
Section: Ram Süreçleriunclassified
See 3 more Smart Citations